Strong demand for early-maturity maize in Kenya - Rutsaert, Pieter; Donovan, Jason (CGIAR Initiative on Market Intelligence, 2023)
In Kenya, most farmers produce maize under rain-fed conditions and purchase hybrid maize seeds on an annual basis. Two factors are especially important in their decisions on which seed to acquire: where the production takes place (i.e., level of rainfall and altitude) and when it takes place (i.e., long- or short-rains season).